Effect of hyperthyroidism and hypothyroidism on coronary microvascular geometry in neonatal and adult rats. - Heron, Marcia Indranee. (University of Ottawa (Canada), 1996)
The coronary microvascular response during pathological growth is important for the maintenance of adequate myocardial oxygenation. The aim of this research was to examine the coronary microvascular response to hyperthyroidism. Capillary geometry was examined in hyperthyroid, hypothyroid, and hypo-hyperthyroid adult male Sprague Dawley rats. Heart rates increased in hyperthyroid and hypo-hyperthyroid rats but decreased in hypothyroid rats compared to control. Adult-onset hyperthyroidism increased absolute and relative heart mass, whereas hypothyroidism decreased these parameters. In hypo-hyperthyroid rats, heart mass increased compared to hypothyroid rats and relative heart mass increased compared to control. Capillary numerical density was maintained in hyperthyroid and hypo-hyperthyroid rats despite increased LV mass, suggesting capillary proliferation. Hypothyroid rats had a larger than expected increase in capillary numerical density compared to control. In hyperthyroid rats, the area of tissue surrounding an individual capillary (capillary domain) decreased for proximal capillaries, whereas in hypothyroid rats domain areas decreased in both proximal and distal regions compared to control. All groups had shorter capillary segment lengths in proximal and distal regions relative to control. PCNA labelling of endothelial cells was significantly increased only in hypo-hyperthyroid rats. These data suggest that both adult-onset hyper- and hypothyroidism induced capillary proliferation. The effect of altered thyroid hormone status on the developing coronary microvasculature was examined in neonatal rats. Long-term effects of neonatal-onset hyper- and hypothyroidism on coronary microvascular geometry and cardiac function were examined in a subset of adult rats in which euthyroidism had been re-established. Neonatal-onset hyperthyroidism enhanced maturation, while hypothyroidism attenuated maturation. Serum T$\sb3$ levels and heart rates increased in hyperthyroid but decreased in hypothyroid rats compared to control. After discontinuing treatment, heart rates were similar between control and previously hypothyroid rats. Occasionally, heart rates remained elevated in previously hyperthyroid rats compared to control. Hyperthyroidism produced ventricular hypertrophy while hypothyroidism slowed cardiac growth. Both neonatal thyroid conditions induced a long-term deficit in LV growth after euthyroidism was re-established. Capillary and arteriolar numerical density, as well as proximal and distal capillary segment lengths, were maintained in hyperthyroid rats despite LV hypertrophy suggesting enhancement of capillary and arteriolar proliferation. Total arteriolar length was greater in hyperthyroid than control rats. With hypothyroidism, capillary numerical density was either maintained or increased compared to control. Total arteriolar length was significantly lower in hypothyroid rats suggesting slowed arteriolar growth. After cessation of treatment, total arteriolar length in previously hyperthyroid rats did not change despite increased LV mass. Previously hyperthyroid rats had increased RV and LV systolic pressure, LV developed and end-diastolic pressure, and +(dP/dt)max (P 0.05). An increased percentage of small arterioles (i.e. 10-30$\mu$m) was observed in previously hypothyroid rats. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.